Correction: The impact of Fosetyl-Aluminium application timing on Karnal bunt suppression and economic returns of bread wheat (Triticum aestivum L.). - Muhammad Arif (Public Library of Science (PLoS), 2021)
[This corrects the article DOI: 10.1371/journal.pone.0244931.].